2019
DOI: 10.1063/1.5126714
|View full text |Cite
|
Sign up to set email alerts
|

Human stroma and epithelium co-culture in a microfluidic model of a human prostate gland

Abstract: The prostate is a walnut-sized gland that surrounds the urethra of males at the base of the bladder comprising a muscular portion, which controls the release of urine, and a glandular portion, which secretes fluids that nourish and protect sperms. Here, we report the development of a microfluidic-based model of a human prostate gland. The polydimethylsiloxane (PDMS) microfluidic device, consisting of two stacked microchannels separated by a polyester porous membrane, enables long-term in vitro cocultivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
16
0
2
Order By: Relevance
“…In this section, we discuss the multiple ways in which CAFs affect the primary PCa microenvironment and tumor growth, particularly regarding ECM modulation, signaling interaction mechanisms with tumor cells and androgen regulation. Different methods have been implemented for the study of prostate epithelial-stromal interactions, such as the in vivo smooth muscle invasion xenograft model to assess the invasive potential of human tumor cells into the smooth muscle/skeletal muscle structures of the diaphragm [112], the differential reactive stroma xenograft model [107], the 3D co-culture of organoids with prostate stromal cells [113], and the novel microfluidic human prostate in a chip ex vivo model [114].…”
Section: Tumor-caf Interactions In Primary Prostate Cancermentioning
confidence: 99%
“…In this section, we discuss the multiple ways in which CAFs affect the primary PCa microenvironment and tumor growth, particularly regarding ECM modulation, signaling interaction mechanisms with tumor cells and androgen regulation. Different methods have been implemented for the study of prostate epithelial-stromal interactions, such as the in vivo smooth muscle invasion xenograft model to assess the invasive potential of human tumor cells into the smooth muscle/skeletal muscle structures of the diaphragm [112], the differential reactive stroma xenograft model [107], the 3D co-culture of organoids with prostate stromal cells [113], and the novel microfluidic human prostate in a chip ex vivo model [114].…”
Section: Tumor-caf Interactions In Primary Prostate Cancermentioning
confidence: 99%
“…The development of the OOC platform can revolutionaries the drug development process. Physiologically relevant mimicking of the microenvironment and ability to incorporate physiological forces affecting niche and co-culturing of multiple types of the cell and Jiang et al 15 Kidney-on-a-chip For predicting the renal tubular reabsorption of various drugs Primary human renal proximal tubule epithelial cells (RPTECs), Sakolish et al 16 Endometrium-on-a-chip For studying the role of hemodynamic forces on endometrial decidualization…”
Section: Lung-on-a-chipmentioning
confidence: 99%
“…29 Further evidence is presented by Kim et al where they suggested a deterministic role for TAZ regulation in upregulation of PDX1+ and enhancement of pancreatic differentiation (Table 1). 47 Due to the increasing interest in guiding stem cell fate over porous membranes in co-culture systems, [49][50][51] the role of substrate disruption in cell differentiation should be considered in these studies. Moreover, these findings can also be employed to help develop more physiologically relevant cellular responses and direct cell phenotype by optimizing the design of porous membranes.…”
Section: Differentiationmentioning
confidence: 99%
“…Due to the increasing interest in guiding stem cell fate over porous membranes in co-culture systems, 49–51 the role of substrate disruption in cell differentiation should be considered in these studies. Moreover, these findings can also be employed to help develop more physiologically relevant cellular responses and direct cell phenotype by optimizing the design of porous membranes.…”
Section: Differentiationmentioning
confidence: 99%